An investigation of the geochemistry and petrology of canal sediments - Dodd, Juliet S. (2000)
Canals are artificial waterways, which are distinct from natural aquatic systems. As a result of their industrial heritage they have experienced high loadings of anthropogenic material, and consequently their sediments tend to have a bulk composition that is distinct from natural sediment. It is therefore expected that the geochemical behaviour of canal sediment may deviate significantly from that of natural sediment. This study investigates and contrasts the geochemistry and petrology of a rural and urban canal sediment, in order to determine the influence of anthropogenic material upon the urban sediment and to gain an understanding of the diagenetic processes operating within the sediments.